Edi Suprayetno - Edi Suprayetno; M. Ridho (Jurnal Manajemen Dan Akuntansi Medan, 2021)
This study aims to analyze the realization of e-SPT Income Tax (PPh) Article 23 revenue of corporate taxpayers and the level of corporate taxpayer compliance on e-SPT Income Tax (PPh) article 23 reporting at Medan Petisah Pratama Tax Office. The research method used in this sudy was descriptive analysis. The data were compiled, interpreted, explained, and analyzed to answer the reseach questions. The type of data used in this study was qualitative data, where the data was obtained from KPP Pratama Medan Petisah from 2017-2019. The results of this study were: 1) The realization of e-SPT PPh Article 23 revenue for corporate taxpayers listed from 2017 tax year to 2019 tax year did not reach significant changes. In 2017, it was gained 384 from the total 12,897 taxpayers listed or 3.0%. In 2018 tax year it was gained 472 from the total listed of 13,449 or 3.5% and in the 2019 tax year it was gained 518 from the total of 14,118 taxpayers listed or 3.7%. 2) The compliance level of corporate taxpayers in reporting e-SPT PPh Article 23 from 2017 tax year to 2019 tax year was also very low and had no significant changes. In 2017 it was gained only 8.6% or 384 from 4,448 of corporate taxpayers listed. In 2018 tax year, there were 10.2% or 472 from 4649 corporate taxpayers listed, and in 2019 tax year it was gained 10.5% or 518 from 4,953 corporate taxpayers listed which reported e-SPT. So it can be stated that the compliiance level wa on non-compliant category